2013
DOI: 10.1080/0267257x.2013.800899
|View full text |Cite
|
Sign up to set email alerts
|

How do consumers co-create their experiences? An exploration in the heritage sector

Abstract: and is the recipient of the Ian Kirk Scholarship. She received her Bachelor of Arts in Psychology and German and her Bachelor of Business in Marketing (Honours) from Monash University. Her areas of interest include co-creation, service and experience marketing and branding. Joanna has published in the Journal of Services Marketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
189
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(227 citation statements)
references
References 80 publications
15
189
0
1
Order By: Relevance
“…Such research has demonstrated that preferences for certain kinds of experiences are not necessarily a priori, and are to an extent also constructed by the consumer/visitor in the course of the experience (Hoeffler & Ariely, 1999). Minkiewicz et al (2014) propose that three meaningful dimensions can be discerned in the co-creation of experience: personalization (ability to adjust a service or product to meet individual customers' needs or preferences), engagement (encouraging a sense of involvement or identification with an offering), and co-production (customer involvement in actively forming the product).…”
Section: Co-creation Of the Tourism Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Such research has demonstrated that preferences for certain kinds of experiences are not necessarily a priori, and are to an extent also constructed by the consumer/visitor in the course of the experience (Hoeffler & Ariely, 1999). Minkiewicz et al (2014) propose that three meaningful dimensions can be discerned in the co-creation of experience: personalization (ability to adjust a service or product to meet individual customers' needs or preferences), engagement (encouraging a sense of involvement or identification with an offering), and co-production (customer involvement in actively forming the product).…”
Section: Co-creation Of the Tourism Experiencementioning
confidence: 99%
“…These two terms are clearly linked in Pine and Gilmore's (1998) experience economy model, which is based on the proposition that consumers assign value to experiences. This model has been adopted by Prahalad and Ramaswamy (2004) in their work on co-creation, and is now emerging in tourism literature as well (Minkiewicz, Evans, & Bridson, 2014).…”
Section: Co-creation Of the Tourism Experiencementioning
confidence: 99%
“…These dimensions include generic features, comfort amenities, program content, staff, facility, food, souvenir, convenience, information, promotion, shopping, ambience of the environment, (Yang, Chen, & Chien, 2014). Minkiewicz, Evans, and Bridson (2014) suggested that personalization (i.e., the ability to change a service or product to meet customers' needs or preferences), engagement (i.e., inspiring a sense of involvement or identification with an offering), and coproduction (i.e., customer participation in developing products) can be recognized in the cocreation experience. For example, customers of the financial insurance industry who help select investment options gain more decision power, which makes the service process smooth, leading to more satisfied customers (Chan, Yim, & Lam, 2010).…”
Section: Research Framework and The Hypothesesmentioning
confidence: 99%
“…We would like to suggest that future research features potential interviews with curators, visitors and participant observations (see for instance Jafari, Taheri and von Lehn, 2013;Minkiewicz, Evans and Bridson, 2014). This might take the form of narrative or thematic analysis to aid in developing a thick description (Geertz, 1973) of the exhibition visit, in order to explore further the dialogic process of the co-creation of visitor experiences within art and heritage marketing.…”
Section: Resultsmentioning
confidence: 99%